STRATEGI PENGEMBANGAN KAWASAN WISATA ALAM MATA AIR PANAS RANA MASAK DI DESA GOLO NDELE KECAMATAN KOTA KOMBA KABUPATEN MANGGARAI TIMUR - Ibes, Melania; Samin, Mikael; Andrinata, Andrinata (Universitas Nusa Cendana, 2025)
The still-rarely-known Rana Masak Hot Spring Natural Tourism Area is a problem in itself. Therefore, an appropriate strategy is needed in the development of the Rana Masak Natural Tourism Area. The method used is a Mixed method, with data collection techniques through observation, documentation, interviews and questionnaires. The results of the study show that the Rana Masak Hot Spring Natural Tourism Area has visual attractions including: hot springs at more than one point, golden yellow limestone rock formations, panoramic rice fields and rivers that soothe the eyes of tourists. Accessibility conditions are still inadequate because they still use dirt paths. The condition of the available amenities is only a park equipped with chairs in a state of disrepair. The strategy that must be implemented is to support an aggressive growth policy by using existing strengths to take advantage of existing opportunities and the development of the Rana Masak Hot Spring Natural Tourism Area is further optimized by strengthening the construction of facilities and accessibility as well as increasing promotion by collaborating with local influencers so that it can become a favorite and sustainable tourist destination.